Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5114/ninp.2012.30262
|View full text |Cite
|
Sign up to set email alerts
|

Poor insight into memory impairment in patients with Huntington disease

Abstract: Huntington disease patients underestimate memory dysfunction. These results add to the previous reports on poor insight in HD in other domains and suggest that anosognosia in HD, albeit usually rather mild, may be a generalized phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 43 publications
2
30
1
Order By: Relevance
“…Furthermore, since HD is a neurodegenerative condition, individual’s in the later stages often exhibit anosognosia, or a lack of insight into one’s own symptoms and deficits (5355). Anosognosia can compromise the reliability of a PRO, highlighting the importance of capturing information from another source (i.e., ClinRO and/or ObsRO).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since HD is a neurodegenerative condition, individual’s in the later stages often exhibit anosognosia, or a lack of insight into one’s own symptoms and deficits (5355). Anosognosia can compromise the reliability of a PRO, highlighting the importance of capturing information from another source (i.e., ClinRO and/or ObsRO).…”
Section: Discussionmentioning
confidence: 99%
“…This measure is designed to capture PROs for individuals with HD. However, there is much discussion in the HD community about an individual's ability to provide reliable self-report data during the later phases of the disease, when both cognitive problems and anosognosia are common 3335. To this end, the general consensus is that self-report measures, by themselves, only capture one component of the clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, their memory is impaired, showing poor retrieval capacity [1]. HD patients have been described as unaware of their motor symptoms, their behavioral disorders, their cognitive deficits [2], [3], [4], [5], [6], [7], [8], but also recently their memory deficits [9]. Although unawareness of memory deficits is a classical clinical feature in patients with Alzheimer's disease (AD) [10], [11], it was recently shown that patients with Parkinson's disease (PD) can report their own memory difficulties through auto-questionnaires [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although unawareness of memory deficits is a classical clinical feature in patients with Alzheimer's disease (AD) [10], [11], it was recently shown that patients with Parkinson's disease (PD) can report their own memory difficulties through auto-questionnaires [12]. Given that both PD and HD are basal ganglia neurodegenerative disorders yielding executive dysfunction and memory retrieval deficits [13], preserved vs. impaired awareness for memory deficits in PD [12] vs. in HD [9] respectively would suggest that unawareness for memory deficit might not depend on striatal dysfunction per se but on another neural basis. If this hypothesis were true, one would expect good awareness of memory deficits at early stage Huntington's disease where degeneration predominates in the striatum [14], [15] and unawareness of these deficits at more advanced stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation